2012
DOI: 10.3892/br.2012.50
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of CCND1 G870A and esophageal cancer susceptibility: A meta-analysis

Abstract: Abstract. The association between the polymorphism of cyclin D1 (CCND1) and esophageal carcinogenicity has been widely examined, however, it remains controversial. To evaluate the importance of CCND1 G870A polymorphism with regard to the risk of esophageal cancer, a meta-analysis was carried out that reviewed the available literature in order to clarify the controversies. This meta-analysis included 1,154 cases and 1,678 controls for CCND1 G870A polymorphism from seven published case-control studies. The odds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…One meta-analysis (Chen et al, 2012) exhibited the statistically significant association between CCND1 G870A polymorphism and a risk for cancers of the digestive tract, including esophageal cancer (Zhang et al, 2003; Cescon et al, 2009). Another meta-analysis suggested that this polymorphism has no significant association with esophageal cancer risk in the Caucasian or the Asian populations (He et al, 2013). There are no substantial data confirming the correlation of this type of polymorphism with cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One meta-analysis (Chen et al, 2012) exhibited the statistically significant association between CCND1 G870A polymorphism and a risk for cancers of the digestive tract, including esophageal cancer (Zhang et al, 2003; Cescon et al, 2009). Another meta-analysis suggested that this polymorphism has no significant association with esophageal cancer risk in the Caucasian or the Asian populations (He et al, 2013). There are no substantial data confirming the correlation of this type of polymorphism with cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies obtained on different populations can be contradictory. The evidence of an association between some rare allele variant and risk of disease can be achieved by the quantitative analysis of available publications – meta-analysis (Yin et al, 2009; Gao et al, 2011; Jiang et al, 2011; Chen et al, 2012; Cui et al, 2012; Li et al, 2012; Zhang et al, 2012; He et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Yang et al also reported that an A870G polymorphism in CCND1 confers an increased risk for breast cancer [ 18 ]. However, He et al revealed that a CCND1 G870A polymorphism has no association with esophageal cancer risk in ethnicity and histology [ 19 ]. Although a number of studies have been performed to assess the association between the CCND1 A870G polymorphism and prostate cancer susceptibility, the conclusions have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%